SULEIMAN NUMAN PASHA (1868-1925) ; HEAD OF THE MEDICAL DEPARTMENT OF THE FIRST WORLD WAR AND GENERAL INSPECTORATES OF THE ARMY MEDICAL DEPARTMENT (HIS LIFE AND MILITARY ACTIVITIES) - Efdal AS (International Journal of Eurasia Social Sciences, 2015)
XIX. Century was a century for the Ottoman Empire when a series of military losses, rebellion and loss of territory, with a high material and spiritual costs, were faced on one hand and the state officials took measures and made innovations for stopping the rot and preventing the fall partially with the pressure of the great powers and partially by their own will on the other hand. The officials, who saw that one of the ways to stop the aforesaid rot was to train educated masses, opened the schools of specialization, giving the education in western sense in several fields and tried to train the staffs, needed by the country. The Imperial School of Medicine, opened in 1827, was the primary one of these schools of specialization. One of the prominent figures, who came through the Imperial School of Medicine which trained the future intellectuals together with the Imperial Military Academy (1834) and Imperial School of Political Science (1859), which were opened in the same century, was Suleiman Numan Pasha. In this study, the life and professional activities of Suleiman Numan Pasha, who went to Germany in a short time after graduating from the Imperial School of Medicine and specialized in military medicine in Germany for about 6 years, made significant contributions to the medical services in the Ottoman Empire Army either in the peacetime or wartime owing to his area of specialization, were examined. The documents, obtained from the Ottoman Archives of The Prime Ministry and Archive of Lodumlu of the Ministry of National Defense as well as the books and articles, a part of which have the characteristics of memory were used during the study.